PENGENALAN GEOGRAFIS KAWASAN LAMPUNG (SATU KAJIAN RINGKAS) - W. Anwar Falah (BRIN, 1995)
The geographic characteristic that the author is primarily concerned with is about changes in the landscape and, accordingly, about the movement of the human population (migration) in this area from time to time, which the author limits to the period of the 'colonisatie' program organized by the Dutch East Indies government in Early 20th century AD The definition of Lampung region in the context of its breadth, the author limits it in this paper, is identical to the definition of the administrative area of the Province of DT. I Lampung. However, the author does not intend to focus specifically on aspects relating to administrative subjects of this area.